PERBANDINGAN TEKNIK PENARIKAN SAMPEL UNTUK ESTIMASI RELIABILITAS - Nusantari, Diah Oga (Jurnal Math-UMB.EDU, 2019)
The purpose of this study is to compare the results of reliability estimation for multiple choice test instrument with data derived from simple random sampling and stratified random sampling using KR-20 formula and Considering one of disadvantages of a multiple choice instrument is  guessing factor, this studi also estimatie reliability by using probability guessing formula as well. The study use quantitative descriptive method,with one way analisys of variance. Data Population is mathematics test results of 69.193 12th grade students fromall over jakarta senior high school wich secondary obtained from BNSP. The results of this study show that, on the same sampling technique,indicates that probability guessing formula estimation are higher compare to KR-20 formula. In terms of  estimate reliability with same formula and data derived from different sampling method, indicate  even by KR-20 formula or probability guessing formula, estimation of reliability will  higher by data derived from simple random sampling Keywords: KR-20 formula, probability guessing formula, sampling technique, simple random sampling, stratified random sampling